Pesantren Transgender: Negosiasi Citra Tubuh di Pondok Pesantren Waria Senin-Kamis Notoyudan Yogyakarta: Transgender Islamic Boarding School: Body Image Negotiation at the Monday-Thursday Waria Islamic Boarding School in Notoyudan, Yogyakarta - Achmad Nur (Fenomena, 2012)
This study describes the intellectual and spiritual journey of transvestites organized by a boarding institution located in the village of Notoyudan, Yogyakarta. This boarding school was founded by Mother Mariyani with the aim of bridging and facilitating transvestites who wish to explore religious knowledge and worship quietly and reverently. From this objective reality, academic interests emerged, including: first, the use of the term "pesantren" (Islamic boarding school) labeled on transgender individuals as a practice of social legitimacy. Second, the religious activities of the students, which emphasize strengthening the mental-spiritual aspect. The research question to be answered is: what body image negotiation is displayed and popularized by the students at the Monday-Thursday Transvestite Islamic Boarding School in Notoyudan Village, Yogyakarta? To answer this question conceptually, two theories are used: first, body image based on Stuart Hall's representation theory, which emphasizes the political representation of the body. Second, the concept of social identity, which emphasizes society's recognition of actions taken by an individual or community. As a foundation for reading and analyzing field data, ethnomethodology is used to understand the basis of social consciousness through negotiation or social interaction by the transvestite students. The findings of this study reveal that the students wish to escape from the captivity of transsexual life, which involves both theological alienation (between the servant and God) and sociological alienation (between the individual and the surrounding community). To escape this alienation, transgender students pursue liberation by filling the knowledge gap about religion through frequent prayers and performing various religious rituals. Behind these efforts, the students also aim to build and create a new image of the transgender community—no longer seen as apostate servants of God but as individuals who also need and are devoted to religion. Studi ini menggambarkan perjalanan intelektual dan spiritual para waria yang terorganisir dalam sebuah lembaga pesantren yang terletak di kampung Notoyudan, Yogyakarta. Pesantren ini didirikan oleh Ibu Mariyani dengan tujuan menjembatani dan memfasilitasi para waria yang ingin mendalami ilmu agama serta beribadah dengan tenang dan khusyuk. Dari realitas objektif ini, muncul ketertarikan akademis, antara lain: pertama, penggunaan istilah pesantren yang dilabelkan pada kaum transgender sebagai praktik legitimasi sosial. Kedua, kegiatan keagamaan para santri yang lebih menekankan pada penguatan aspek mental-spiritual. Pertanyaan penelitian yang ingin dijawab adalah negosiasi citra tubuh apa yang ditampilkan dan dipopulerkan oleh para santri di Pesantren Waria Senin-Kamis di Kampung Notoyudan, Yogyakarta? Untuk menjawab pertanyaan tersebut, digunakan dua teori: pertama, citra tubuh yang berlandaskan pada teori representasi Stuart Hall, yang menekankan representasi politik tubuh. Kedua, konsep identitas sosial yang menekankan pengakuan masyarakat terhadap tindakan yang dilakukan oleh seseorang atau komunitas. Sebagai dasar untuk membaca dan menganalisis data di lapangan, digunakan pendekatan etnometodologi untuk memahami landasan kesadaran sosial melalui negosiasi atau interaksi sosial yang dilakukan oleh para santri waria. Temuan dalam penelitian ini menunjukkan bahwa para santri ingin keluar dari kehidupan transgender yang teralienasi, baik secara teologis (alienasi antara hamba dan Tuhannya) maupun sosiologis (alienasi antara individu dan masyarakat sekitar). Untuk keluar dari alienasi ini, para santri transgender melakukan pembebasan melalui pengisian kesenjangan pengetahuan agama dengan banyak berzikir dan melakukan berbagai ritual keagamaan. Di balik upaya tersebut, para santri juga ingin membangun citra baru komunitas transgender, yaitu sebagai hamba yang tidak lagi dianggap murtad tetapi juga membutuhkan dan taat beragama.